Vaginal colonization, vertical transmission rate, antimicrobial susceptibility profile, and associated factors of potential neonatal pathogens among pregnant women at public health facilities of Northeast Ethiopia - Shimeles, Getnet; Gedefie, Alemu; Motbainor, Hilina; Genet, Chalachew (Frontiers in Public Health, 2025)
BackgroundVaginal colonization by pathogenic bacteria increases the risk of bacterial infections such as sepsis, which is associated with high neonatal mortality. More than half a million newborn deaths occur globally each year due to infections that lead to sepsis. However, the problem is worsening in Ethiopia the evidence of vaginal colonization and vertical transmission is scarce.MethodsA healthcare facility-based cross-sectional study was conducted in Dessie town from April 1 to June 30, 2023, among 348 pregnant women and their newborns. Socio-demographic, clinical, and related data were collected using a pre-tested semi-structured questionnaire. Vaginal swab samples from pregnant women and pooled external ear, nasal area, and umbilical swab samples from the newborns were collected and transported using Amies transport media. Samples were inoculated into blood agar, Todd Hewitt selective enrichment broth, and MacConkey agar for bacterial isolation, and Sabouraud Dextrose Agar and CHROM Agar for Candida species isolation. The antimicrobial susceptibility was performed on isolates using the Kirby-Bauer disc diffusion technique. Data was analyzed by SPSS version 25.0. Logistic regression model was used to identify the associated factors. Finally, variables with p < 0.05 and their 95% confidence interval were considered statistically significant.ResultsA total of 348 pregnant women attending vaginal delivery were included in the study. The maternal colonization and vertical transmission rates were 55.5% (193/348) and 53.9% (104/348), respectively. The most frequent potential pathogen among pregnant women was Escherichia coli (27.6%), followed by Candida spp. (14.1%), and Klebsiella spp. (6%). Similarly, the predominant isolates in the newborns were E. coli (16.4%), Candida spp. (6.3%), and Klebsiella spp. (3.6%). The overall multidrug resistance levels of potential pathogens were 37.3%. Living with domestic animals (p = 0.001), having premature rupture of membrane (p = 0.010) and history of urinary tract infection (p = 0.013) were significantly associated with maternal colonization. Potential pathogen colonization newborn was significantly associated with duration of labor (p = 0.024) and low birth weight (p < 0.001).ConclusionThe finding of the present study revealed that vaginal colonization and vertical transmissions of potential pathogens and their antimicrobial resistance is still a significant problem. This alarms the urgency of evidence based-intervention to improve maternal and neonatal health.